European Experience of Social Partnership in the Labour Field: Perspectives for the Republic of Moldova - Irina Nicolaescu; Valentina Teosa (CES Working Papers, 2012)
European integration is not a slogan, a political discourse or a foundation for the political platform of political parties. European integration includes concrete directives of action to be taken into account by all states. One of the most important of them might be considered the social partnership in the labour field. Under current circumstances, the need to study relations established within social partnership, factors contributing to social dialogue development and fulfillment of social partnership potential within existing political and socio-economic reforms increased. Analysis of European dimension of Moldovan social partnership evolution is essential for further democratization of labour field and European perspectives of the country.
Keywords: J5; 330; social partnership; trade unions; labour market; new social partnership; employers; employees; labour conflict Romania